Desempenho de cabritos da raça Saanen e mestiço Saanen x Boer abatidos em duas idades - Firmino, Salenilda Soares (Universidade Federal Rural do Semi-Árido, 2017)
Abstract: The objective of this study was to evaluate the quality of the meat, the zootechnical and economic yields of carcass constituents and non-carcass of Saanen and Saanen x Boer mongrel (1/2 Saanen x 1/2 Boer) slaughtered at 30 and 60 Days. They have been used 32 male kids, fed on naturally receiving solid food from 30 until 60 days. It was used an experimental design entirely randomized with four treatments, (Saanen male kids slaughtered within 30 days, Saanen x Boer mixed male kids slaughtered within 60 days). After the slaughter were measured the measures of Ph, temperature while slaughter and after 24 hours. The meat was submitted by microbiological analysis where were carried out counting of bacteria, thermotolerant coliforms, Salmonella research spp. E Staphylococcus spp. Mesophiles and Psychrotrophic. It was carried out the sensory test to assess acceptance and intention of purchase. They have analyzed the physical-chemical parameters with color (L* luminousity (black-white), a* content of red (green/red) and b* content of yellow (blue/yellow), capacity of water retention (CWR), loss of weight in cooking (LWC), shear force (SF), humidity, mineral material, protein, grease and Thiobarbituric acid test (TBARS) They have been carried out also the parameters related to carcass and the non-carcass components income. The assessment of economic performance included in the calculation of the cost indicators, incomes and measures of economic results. All variable ones were submitted the analysis of variance to test F the 5% of probability and Tukey test. It was not observed meaningful difference among the treatments (P>0,05 ) for the values of Ph and the carcasses temperature pre and post cooling. It was not observed microorganisms growth of Staphylococcus spp; Salmonella spp. Neither quantification of Aerobic, Mesophiles and Psychrotrophic bacteria in any treatments. The parameters related to meat color, capacity of water retention, loss of weight for cooking, and shear force did not show meaningful differences ( P>0,05) for the breed effect, however all ones have shown meaningful difference (P>0,05) for the male kids age effect. The values found for the humidity content, mineral material, protein, grease and TBARS did not differ (P>0,05) Statistically between itself for breed x age effect. In sensory analysis only was observed meaningful difference for the appearance and meat color features. (P<0,05) The mixed animals meat have gotten better acceptance by the tasters. Meaningful differences were not observed (P>0,05) among the treatments, for the variances of carcasses and non-carcasses components features. The differences found were for animals age, in which the male kids slaughtered within 60 days have shown better results in comparison to 30 days. The results obtained in this research have shown that the animals slaughtered within 60 days have shown better results for the quality of meat, as well, weight gain and carcass income. It showing itself as more economically advantageous option to producer
Performance of kids goats of the Saanen race and Saanen x Boer mestication abatidos in two ages
Keywords: Animais jovens; Abate; Carne caprina; Custos; Young animals; Slaughter; Goat meat; Costs; CIENCIAS AGRARIAS::MEDICINA VETERINARIA